A case of added value of 123I-mIBG SPECT/CT imaging in the diagnosis of a pheochromocytoma extending into the left adrenal vein. Issue 3 (4th May 2017) - Paques, Florence; Hamoir, Etienne; Lovinfosse, Pierre; Hustinx, Roland; Withofs, Nadia
Abstract: We present the case of a 48-year-old patient with a left adrenal incidentaloma found on computed tomography (CT) for which the diagnosis of pheochromocytoma was confirmed by a 24-hour urinary dosage of norepinephrine. The 123 I-mIBG scintigraphy showed a high uptake of 123 I-mIBG in the left adrenal gland and, additionally, the single photon emission computed tomography combined with a low-dose CT (SPECT/CT) suggested the extension into the adrenal vein. The diagnostic CT and magnetic resonance images agreed with these findings and the subsequent surgery confirmed the vascular invasion.